2011
DOI: 10.4269/ajtmh.2011.10-0498
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Intense Malaria Transmission in Northern Uganda

Abstract: Abstract. Recent reports of reductions in malaria transmission in several African countries have resulted in optimism that malaria can be eliminated in parts of Africa where it is currently endemic. It is not known whether these trends are global or whether they are also present in areas where political instability has hindered effective malaria control. We determined malaria parasite carriage and age-dependent antibody responses to Plasmodium falciparum antigens in cross-sectional surveys in Apac, northern Ug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 47 publications
9
35
1
Order By: Relevance
“…These findings confirm previous reports from other countries in Southeast Asia and Africa, where use of molecular techniques showed a high complexity of infections, i.e., high proportions of mixed infections and high occurrence of P. malariae and P. ovale compared with that detected by standard microscopy 7,8,1618…”
Section: Discussionsupporting
confidence: 91%
“…These findings confirm previous reports from other countries in Southeast Asia and Africa, where use of molecular techniques showed a high complexity of infections, i.e., high proportions of mixed infections and high occurrence of P. malariae and P. ovale compared with that detected by standard microscopy 7,8,1618…”
Section: Discussionsupporting
confidence: 91%
“…Although true baseline data are lacking, a 2009 study in Apac indicated a 55.8% parasite prevalence rate in children 5 years. 16 The sampling methods are different between this survey and our survey (testing of community members at health centers versus testing during household interviews), but this prevalence is substantially higher than the 37.0% parasite rate that we found in our survey nearly 2 years later after two additional rounds of IRS had been conducted.…”
Section: Discussionmentioning
confidence: 60%
“…Parasite prevalence was measured to be 79.8% among children 1-9 years of age in 1999 14 and 55.8% among children under 5 years old in 2009. 16 The US President's Malaria Initiative (PMI) began supporting IRS in northern Uganda in 2007, starting with four highly endemic districts (Kitgum, Pader, Gulu, and Amuru) and further expanding to two more districts in 2008 (Apac and Oyam). The current program continues to cover those 6 districts (now 10 districts after administrative reorganization in 2010) and has shifted from use of DDT and pyrethroids to carbamates as a result of resistance data from entomological monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-sporozoite antibody levels were high during the rainy season and decreased significantly to low levels in the dry season (Table 3). Anti-AMA1 antibody seroprevalence was not different between seasons, confirming the persistence of these antibodies and the reduced likelihood of anti-AMA1 antibodies fluctuating with short term changes in transmission intensity [20,37]. …”
Section: Discussionmentioning
confidence: 91%